Maternal Docosahexaenoic Acid (DHA) Supplementation and Offspring Neurodevelopment in India (DHANI). (29th May 2020) - Khandelwal, Shweta; Kondal, Dimple; Chaudhary, Monica; Patil, Kamal; Metgud, Deepa; Joglekar, Sandesh; Kamate, Mahesh; Divan, Gauri; Gupta, Ruby; Prabhakaran, Dorairaj; Tandon, Nikhil; Ramakrishnan, Usha; et al.
Abstract: Objectives: Evidence suggests that low maternal levels of docosahexaenoic acid (DHA; 22:6n-3), a long-chain omega-3 fatty acid, are associated with suboptimal offspring brain development. Indian diets are low in DHA. We assessed the impact of maternal DHA supplementation on N euro-development of I ndian infants (DHANI ) at 12 months (mo). Methods: Healthy pregnant women (£20 weeks of singleton gestation; n  = 957; mean age = 23.5 y) were randomized to receive either 400 mg/d of DHA or a placebo from enrolment till 6 months postpartum. The mother-child dyads were followed through infant age 1 year. Development Quotient (DQ) scores were assessed at ages 6- and 12-mo using the validated Development Assessment Scale for Indian Infants (DASII). Results: The two groups were well-balanced at baseline. 72.6% of women took >90% of their assigned treatment. 25 serious adverse events, found unrelated to intervention, were reported (DHA group = 16; placebo = 9). Of the 902 live births, 878 were followed to 12 mo; the DASII was administered to 863 infants. Intent-to-treat 12 mo mean DQ scores (SD) (DHA, control) and difference (DHA-control) were: 96.6 (12.2), 97.1 (13.0) and −0.46 (95% CI −1.23, 2.14; P  = 0.6), respectively. Similarly, at the end of the supplementation period at 6 mo postpartum, there were no differences in mean DQ scores by intervention (difference 1.15 (95% CI −2.64, 0.35; P  = 0.13). Conclusions: Supplementing mothers through pregnancy and lactation with 400 mg/d DHA did not impact offspring neurodevelopment at 6 or 12 mo of age in this Indian setting. Deeper insights into maternal dietary patterns, young child feeding practices, home environment, and the interactions amongst these factors are warranted to understand what shapes early neurodevelopment. Funding Sources: Funded by Wellcome Trust-DBT India Alliance (Dec 2015-Dec 2020). The Young Scientist Award by DST SERB India (2013–16) helped us establish DHANI trial partially.